Scripts for analysing genomic data and ASE in Capsellla grandiflora - Benjamin Laenen (Stockholm University, 2016)
An example script with all program versions and
flags used for bioinformatic analyses in Steige et al. 2017 PNAS.
Keywords: 60409 Molecular Evolution; Evolutionary Biology; Evolutionary Biology; Evolutionsbiologi; Biochemistry; Biokemi